Attitudes of the Jordanian Public towards Advertisements by Artists in Satellite Stations and their Impact on their Purchasing Behavior: A Field Study - Al-Alimat , Farhan Rashid; Bani Hani , Saja Khaled (Jordan Journal of Social Sciences, 2023)
This study aimed to identify the Jordanian public’s attitudes towards advertisements by artists in satellite stationsand their impact on their purchasing behavior. The study falls within the scope of descriptive research, employing a survey methodology. A questionnaire was distributed among a sample of 491 Jordanian individuals residing in the Northern region, chosen using convenience sampling. The study applied the Dependency Theory and the AIDA model, reflecting them in the study's questions and objectives. The study reached the following results: It was found that there was an effect of advertisements by artists on satalleite stations on the purchasing decision, as the Jordanian public preferred advertisements of Arab artists and watched them on Arab satalleite stations in a large percentage, and that the most important factors attracting attention are colored photographs, the product presentation method, and the celebrity's personal charisma. Key factors in arousing interest included the presentation method, clear and appealing product display, and the use of a concise method to express the product suitable for various ages and education levels. The cognitive effects on the sample population included an increase in their knowledge of different cultures and a proper assessment of the product. Emotional effects involved a sense of satisfaction, and behavioral effects stimulated them towards making a purchase. A statistically significant relationship resulted between the degree of Jordanian audience engagement with celebrity advertisements on the stations and the existence of a statistically significant relationship between the effects (cognitive, emotional, and behavioral) of artists’ advertisements on satellite stations on the Jordanian public and the purchasing behavior.